Effects of drag factor on physiological aspects of rowing - Kane, D. A.; Jensen, R. L.; Williams, S. E.; Watts, P. B. (International Journal of Sports Medicine, 2008)
This study examined the effects of two resistances, or "drag factors" on selected physiological variables during incremental progressive rowing tests (seven 3-min stages) on a Concept2® ergometer. Subjects were seven male and seven female university club rowers. Their mean age, body mass and height were 19.6 ± 1.5 years, 72.7 ± 8.0 kg, and 172.2 ± 7.5 cm, respectively. Progressive tests were conducted using drag factors 100 (D100) and 150 (D150) before the spring racing season. Values were determined for the following physiological variables: ventilation (V·E), oxygen uptake (V·O2), heart rate (HR), blood lactate concentration (BLC), respiratory exchange ratio (R) and rowing economy (W/V·O2). Comparisons across all six submaximal stages showed no significant difference between D100 and D150 for any of the variables measured (p > .05). Maximal V·Emax was significantly greater at D100 than D150 (p < .02). Maximal V·O2, HR, BLC, R, stroke rate (SR) and W/V·O2 were greater at D100 than at D150, though not significantly so. The mean D100 - D150 differences in V·E and SR for each stage were significantly correlated (r = 0.76, p < .01), suggesting drag factor may affect V·E via SR.